Cutaneous metastases during an aggressive course of Xp11.2 translocation renal cell carcinoma in a teenager. Issue 9 (3rd March 2014) - Sudour‐Bonnange, Helene; Leroy, Xavier; Chauvet, Marie‐pierre; Classe, Marion; Robin, P. M.; Leblond, Pierre
<x xml:space="preserve">Abstract</x> We reported a rare case of cutaneous metastases of renal cell carcinoma (RCC) with an Xp11.2 translocation in a 15‐year‐old female. Clinicians should be aware of the possibility of this uncommon site of metastasis, which can indicate multivisceral dissemination of the disease. We discuss the feasibility and opportunity of treating such a patient with multiple line of tyrosine kinase inhibitor (TKI) targeting vascular endothelial and platelet‐derived growth factor receptors. Pediatr Blood Cancer 2014;61:1698–1700. © 2014 Wiley Periodicals, Inc.